Psychological aspects in children and parents of children with chronic kidney disease and their families - Alemsungla Aier; Priya Pais; Vijaya Raman (The Korean Pediatric Society, 2022)
Pediatric chronic kidney disease (CKD) is a chronic illness that affects the overall quality of life of patients during childhood. This article highlights the psychological and social burden of CKD in patients and their families. Patients with CKD and their families require comprehensive treatment for psychosocial problems. Therefore, it is crucial for pediatricians to screen for these issues and refer patients and their families for therapy. Tools that are short, easy to administer, and easy to score, such as the Pediatric Quality of Life Inventory or the Childhood Depression Inventory, can be utilized during routine clinical appointments. Reducing the negative impact of CKD on the family will improve the well-being and coping skills of patients and their families.